Rotation of the Mass Donors in High-mass X-ray Binaries and Symbiotic Stars - K. Stoyanov; R. Zamanov (Acta Polytechnica CTU Proceedings, 2015)
Our aim is to investigate the tidal interaction in High-mass X-ray Binaries and Symbiotic stars in order to determine in which objects the rotation of the mass donors is synchronized or pseudosynchronized with the orbital motion of the compact companion. We find that the Be/X-ray binaries are not synchronized and the orbital periods of the systems are greater than the rotational periods of the mass donors. The giant and supergiant High-mass X-ray binaries and symbiotic stars are close to synchronization. We compare the rotation of mass donors in symbiotics with the projected rotational velocities of field giants and find that the M giants in S-type symbiotics rotate on average 1.5 times faster than the field M giants. We find that the projected rotational velocity of the red giant in symbiotic star MWC 560 is v sin i= 8.2±1.5 km.s−1, and estimate its rotational period to be Prot<>/sub = 144 - 306 days. Using the theoretical predictions of tidal interaction and pseudosynchronization, we estimate the orbital eccentricity e = 0.68 − 0.82.